Sex differences in the prevalence of high-risk oral and anal human papillomavirus infections among heterosexually active populations in Ibadan, Nigeria - Morhason-Bello, Imran; Bello, Yusuf; Oke, Deborah; Daniel, Adekunle; Adisa, Akinyele; Fowotade, Adeola; Zheng, Yinan; Akinyemi, Joshua; Adewole, Isaac; Pavon, Miquel A.; Murphy, Robert; Hou, Lifang; et al. (Frontiers in Reproductive Health, 2025)
PurposeTo determine sex differences in the prevalence of oral and anal high-risk HPV infections among heterosexually active males and females in Ibadan.MethodsThis was a secondary analysis from the Sexual Behavior and HPV Infections in Nigerians in Ibadan (SHINI) study that involved sexually active males and females aged 18–45 years. After a face-to-face interview, samples were collected from the mouth, cervix, vulva, and anus by a sex-matched trained nurse. High-risk HPV (hrHPV) in oral or/and anal sites were primary outcome variables, profiled by AnyplexTM II HPV28 assay. The participants' demographic characteristics, sexual behaviors, and social lifestyle were included as explanatory variables. The chi-square or Fisher exact test was used to investigate the association between the presence of hrHPV and the participants' characteristics. Multivariable logistic regression was conducted to test the association between the sex of participants and each of the primary outcome after adjusting for potential confounders. Statistical significance was set at p < 0.05.ResultsA total of 625 females including 310 females in general population (FGP) and 315 female sex workers (FSWs) and 316 males were recruited. Oral hrHPV prevalence was higher among FGP and FSWs than among males (10.5% vs. 14.9% vs. 3.6%, p < 0.001), as was anal hrHPV prevalence (39.3% vs. 60.8% vs. 6.7%, p < 0.001). More FGP (7.5%) and FSWs (13.0%) than males (0.9%) had hrHPV at both oral and anal sites (p < 0.001). Males had significantly lower odds of oral hrHPV [adjusted odds ratio (aOR) = 0.43, 95% CI: 0.15–1.24] than FSWs and FGP [aOR = 1.70, 95% CI: 0.62–4.63]. The odds of anal hrHPV was significantly lower among males [aOR = 0.05, 95% CI: 0.03–0.08] compared to FSWs and FGP [aOR = 0.42, 95% CI: 0.30–0.58].ConclusionOral hrHPV, anal hrHPV, and hrHPV at both sites were more prevalent in females than in males in the heterosexually active population. These findings highlight the importance of developing targeted HPV prevention strategies that account for sex-specific risk factors and the potential biological underpinnings contributing to these disparities.